Retention and Predictors of Attrition Among HIV-infected Children on Antiretroviral Therapy in Côte d'Ivoire Between 2012 and 2016. Issue 4 (23rd January 2023) - Touré, Fatoumata; Etheredge, Gina D.; Brennan, Claire; Parris, KaeAnne; Diallo, Mamadou Otto; Ouffoue, Ange Fulgence; Ekra, Alexandre; Prao, Herve; Assamoua, N'Da Viviane; Gnongoue, Christian; Kone, Foungnigue; Koffi, Christian; et al.
Abstract : Background: An estimated 21, 000 children 0–14 years of age were living with HIV in Côte d'Ivoire in 2020, of whom only 49% have been diagnosed and are receiving antiretroviral therapy (ART). Retention in HIV care and treatment is key to optimize clinical outcomes. We evaluated pediatric retention in select care and treatment centers (CTCs) in Côte d'Ivoire. Methods: We retrospectively reviewed medical records using 2-stage cluster sampling for children under 15 years initiated on ART between 2012 and 2016. Kaplan-Meier time-to-event analysis was done to estimate cumulative attrition rates per total person-years of observation. Cox proportional hazard regression was performed to identify factors associated with attrition. Results: A total of 1198 patient records from 33 CTCs were reviewed. Retention at 12, 24, 36, 48 and 60 months after ART initiation was 91%, 84%, 74%, 72% and 70%, respectively. A total of 309 attrition events occurred over 3169 person-years of follow-up [266 children were lost to follow-up (LTFU), 29 transferred to another facility and 14 died]. LTFU determinants included attending a "public-private" CTC [adjusted hazard ratio (aHR) 6.05; 95% confidence interval (CI): 4.23–8.65], receiving care at a CTC without an on-site laboratory (aHR: 4.01; 95% CI: 1.70–9.46) or attending a CTC without an electronic medical record (EMR) system (aHR: 2.22; 95% CI: 1.59–3.12). Conclusions: In Cote d'Ivoire, patients attending a CTC that is public-private, does not have on-site laboratory or EMR system were likely to be LTFU. Decentralization of laboratory services and scaling use of EMR systems could help to improve pediatric retention.